Environmental and gender impacts of land tenure regularization in Africa: Pilot evidence from Rwanda - Daniel Ayalew Ali; Klaus Deininger; Markus Goldstein (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Although recent developments greatly increased interest in African land tenure, few models to address these issues at the required scale have been identified or evaluated. Rwanda's nation-wide land tenure regularization programme is of great interest. A discontinuity design with spatial fixed effects that is used to evaluate the pilot for this programme points to three main effects; namely, (i) improved land access for legally married women and better recordation of inheritance rights; (ii) significant and large investment impacts that are particularly pronounced for women; and (iii) a reduction in land market activity rather than distress sales. Implications for programme design and policy are discussed.
Keywords: J16; O13; Q12; Q15; 330; gender; agricultural investment; land administration; Rwanda